Infinity and Beyond? Learning How to be Finite - Jennifer Bunker (Public Reason)
This article discusses the newly added Chapter 16 and Chapter 17 of Adrian W. Moore’s latest edition of The Infinite from 2019. The article interprets Moore’s focus on metaphysical infinity and finitude via his trialogue between Spinoza, Hegel, and Nietzsche. Then, it continues to examine Moore’s mode of addressing nihilism, which consists of reckoning with the infinite as a concept we appeal to when trying to express the insights which sustain value and our moral lives. Following this discussion, four questions are posed to Moore: two regarding his interpretation of the history of philosophy, upon which his views are based; and two regarding his own views. One question focuses on differentiation in Spinoza. The second question concerns the interpretation of Nietzsche’s Eternal Return. The third asks for a motivation for superseding Nietzsche’s finitism. The fourth calls into question the strength of Moore’s proposal of “reckoning with” the infinite.